Navigating Uncertainty in Epidemic Contexts with Reinforcement Learning - Ondula, Elizabeth Akinyi (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
My research integrates stochastic epidemic models with reinforcement learning to develop effective strategies or policies to inform operational decisions. The objective is to refine policies that are attuned to diverse outbreak dynamics and to offer a tool for informed planning in real-world settings.